MICROBIOLOGICALCHARACTERISTIC AND FORMALIN PRESENCEIN DRIED SALTED FISH SOLD ATTHE TRADITIONAL MARKETSIN PEKANBARUCITY - Pramana, Ilham; Leksono, Tjipto; Sari, N. Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was aimed to determine halophilic microbial contamination and the presence of formalin in dried salted fish sold at 3 traditional markets selected in Pekanbaru City. The method used in this study was a survey method conducted directly to the retailing traditional markets by using purposive sampling method. There were 36 samples of dried salted fish collected from the varied sellers and markets analyzed in the laboratories for the existence of halophilic bacteria, thecontent of formaldehyde, and the sensory evaluation. The results showed that there were 3 samples of salted fish contaminated by halophilic bacteria and 9 samples of salted fish containing formalin. There were 6 of 36 samples (16.7%) dried salted fish originated from North Sumatra and 3 of 36 samples (8.3%) dried salted fish originated from West Sumatracontaining formalin. Based on thesensory evaluation, there were some differences indicated between the dried salted fishcontaining formalin and those were not contain formalin, in terms of their appearance, smell, taste and texture.Â Keywords : Dried salted fish, formaldehyde, halophilicbacteria , traditional market